2022
DOI: 10.46557/001c.29979
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Success Factors of the Green Bond Market for Sustainable Development in the COVID-19 Era

Abstract: This paper attempts to identify the most important factors for the success of the green bond market during the COVID-19 pandemic. Using an interactive management approach, we find that the legal framework for green bond operation and the interest rate of green bond are the major factors in determining the success of the green bond market during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In other study, Loffler et al (2021) analyzed about 182,000 bonds from 650 international issuers and confirmed that economic stability and government's policies are two important elements to have a successful GB market. Rasoulinezhad (2022) identified the chief elements to expand the GB efficient market to make positive influence on economic activities. The major findings revealed that through a transparent regulations and marketbased mechanism, the GB market can provide suitable conditions to promote economic performances and productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other study, Loffler et al (2021) analyzed about 182,000 bonds from 650 international issuers and confirmed that economic stability and government's policies are two important elements to have a successful GB market. Rasoulinezhad (2022) identified the chief elements to expand the GB efficient market to make positive influence on economic activities. The major findings revealed that through a transparent regulations and marketbased mechanism, the GB market can provide suitable conditions to promote economic performances and productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the reasons for this is the use of inappropriate policies and tools in improving energy efficiency and developing projects related to this index. Many researchers like Tu et al ( 2020 ) and Rasoulinezhad ( 2022 ) have indicated that to develop energy efficiency projects countries should move toward developing the market of green financing instruments such as green bonds. Another group of previous studies (e.g., Yoshino et al 2021 ; Chien et al 2021 ) insists that proper use of green financial policies, such as establishing a green (carbon) tax, can open the way to improve the energy efficiency index in the countries of the world.…”
Section: Introductionmentioning
confidence: 99%